STUDI MENGENAI KEBERADAAN PEDAGANG KAKI LIMA (PKL) DI PASAR AUR KUNING KOTA BUKITTINGGI DALAM KONSEP ISLAM - ZULWIDA RAHMAYANI -; Nila Pratiwi (Jurnal Tunas Pendidikan, 2018)
Street vendors (PKL) are one of the most popular informal sectors that are able to provide new jobs. In terms of Islamic law, the practice of buying and selling carried out by street vendors is a legitimate and lawful transaction to do if it meets the requirements and harmonizes its sale. This type of research is descriptive qualitative by using primary and secondary data collection with snowball sampling. . The results of the study are the reasons that influence the street vendors to prefer to trade outside the kiosk because they are not permanent traders, the merchandise is simple and can be transported by two-wheeled vehicles. In addition, goods are also sold quickly because they are easy to reach and do not need to enter the shopping area and do not need to pay kiosk rent. The impact caused by street vendors is disrupting traffic resulting in congestion, lack of cleanliness in the market environment and triggering criminal acts. The policy carried out by the government is to control and reinforce the regulations regarding the control of street vendors. According to Islamic law, a buying and selling system that utilizes public facilities including those that are not permitted, even though the terms of sale and purchase are considered valid. Likewise, the government is allowed to issue regulations governing the prohibition of selling on the street, if it is considered to disturb or endanger the passers-by. . When there are elements that are not appropriate in the practice of buying and selling, then it might shift the concept of halalness from the transaction made